Seeder-fertilizer performance with two furrowing mechanisms and sowing speed - Viegas Neto, Antonio Luiz; Souza, Cristiano Márcio Alves de; Arcoverde, Sálvio Napoleão Soares; Lima Junior, Izidro dos Santos de; Piletti, Lígia Maria Maraschi da Silva (Revista Agrogeoambiental, 2020)
The displacement velocity of the tractor-seeder set, associated with the furrowing mechanism, influences the plant distribution and the establishment of a correct plant stand in the field. The objective of this study was to evaluate the operational performance of a seeder-fertilizer in the non-tillage sunflower crop, according to sowing speeds and furrow mechanisms. The experimental design used was the randomized blocks, with treatments arranged in a split-plot scheme, where the plots were the furrowing mechanisms (chisel openers and double disk) and the subplots were the sowing speeds (3.2; 4.6; 6.2 and 7.0km h-1), with three replicates. The following were determined in this study: the emergence speed index, the emergence in the field, the average distance between the plants, plant height, plant population and the longitudinal distribution of plants. Sunflower sowing using a chisel openers provides greater emergence in the field, emergence speed index and, consequently, greater plant population. Sowing speed ranging from 3.2 to 7.0km h-1 do not influence field emergence, emergence speed index, height and population of sunflower plants.